Dual Response to Light and Heat of a Metal–Organic Rotaxane Network Featuring Flexible Viologen‐Derived Structs - Jin, Qiu‐yan; Meng, Liao; Zhang, Zhi‐hui; Liang, Yuan‐yuan; Jin, Wei; Hu, Kong‐qiu; Yuan, Li‐yong; Chai, Zhi‐fang; Mei, Lei; Shi, Wei‐qun (Advanced functional materials, 2023)
Metal–organic rotaxane compounds (MORCs) with supramolecular (pseudo)rotaxane motifs as main structures have inherent dynamic character, but their potential as responsive molecular machines is largely hampered by poor responsiveness to external stimuli. In this study, using a multi‐functionalized pseudorotaxane linker that combines two kinds of functionalities, a novel MORC, U‐bpybc‐CB8 (U refers to uranyl, bpybc refers to 1, 1’‐bis(4‐carboxybenzyl)‐4, 4’‐bipyridinium, and CB8 is cucurbit[8]uril), with multi‐responsive capability that can respond to both light and thermal stimuli, is reported. The characterization, combining spectra measurements and single‐crystal X‐ray diffraction, shows that, due to the involvement of viologen‐functionalized flexible organic dicarboxylate guest molecule in the CB8‐ involved pseudorotaxane ligand, the resultant uranyl‐based MORC exhibits photochromic behavior after UV or visible light irradiation. More interestingly, it is revealed that the exceptional thermal response of U‐bpybc‐CB8 as temperature increases from 170 to 270 K, i.e., volume expansion followed by contraction after the inflection temperature of ≈230 K, can be stemmed from the lattice flexibility of this metal–organic supramolecular network. The dual responsiveness of MORCs reported here demonstrates the potential of such supramolecular assemblies as smart molecular components like sensors and switches that respond to light irradiation or temperature changes.